Implementing Waterfall Methodology in Eidos Website Development for Animal Welfare Enhancement - Hanif Pradika Indradi; Gina Cissy Aprilia; Donny Karunia Pratama; Adam Hermawan; Asep Nuryadin (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Indonesia is ranked third in animal ownership in Asia, or almost 50% of the Indonesian population has pets, but with the high level of animal ownership there are still pet owners who do not know how to care for animals, have obstacles in giving up or adopting pets, and have empathy for animals. abandoned pets, but unable to provide direct assistance due to certain conditions and time. The aim of this research is to develop a website-based platform called Eidos so that people, especially animal lovers, can adopt, donate, discuss, find the nearest animal service location, read information about pets, and buy pet needs. This website development was carried out using the waterfall method . After product development is complete, implementation will be carried out through direct outreach to animal lovers. The results of socialization show a positive response, able to meet their needs, and in accordance with Eidos' expectations, animal lovers can help other pets and care for their pets easily, quickly and safely.